ANALISA PENGARUH KECEPATAN PUTARAN PADA MESIN PENGADUK BAHAN UNTUK PUPUK ORGANIK DAN MEDIA TANAM TERHADAP WAKTU DAN HASIL PUTARAN (Di KOREM 044/GAPO, Desa Rambutan Kabupaten Banyuasin) - Agus, Rizsky Agus Frasdianata; Azharuddin, Azharuddin; Effendi, Sairul (MACHINERY Jurnal Teknologi Terapan, 2023)
This mixing machine for organic fertilizers and planting media is made to make it easier for farmers and industry to mix organic fertilizers and planting media, so that the estimated time of mixing materials for organic fertilizers and planting media by manual method which takes a relatively long time can be minimized, it is necessary to have a the tool is technically and economically acceptable by the communityThe method used is an experimental method by designing machines directly at the Polsri Mechanical Engineering workshop.This study uses technical analysis calculations as data calculations and analysis which consists of 5 kg of organic waste + 30 liters of water with a time variation of 2 minutes, 4 minutes, 7 minutes, and 9 minutes using a power of 2650 rpm. Each treatment was repeated 4 (four) times so that 15 trials were obtainedIn an average time of 5.5 minutes, it produces 33.44 liters of material for liquid organic fertilizer that has been stirred. Then it can be seen that the efficiency of the material mixing machine for organic fertilizer and planting media 42.80%